Lintnerization of banana starch isolated from underutilized variety: morphological, thermal, functional properties, and digestibility - Aparicio Saguilan, Alejandro; Valera Zaragoza, Mario; Perucini Avendaño, Madeleine; Páramo Calderón, Delia Esther; Aguirre Cruz, Andrés; Ramírez Hernández, Aurelio; Bello-Pérez, L. A. (Taylor & Francis, 2014)
The effect of lintnerization on the banana starch of the Roatán cultivar from acid hydrolysis at 3, 5, and 7 days on the starch digestibility and morphological and thermal features was evaluated. Acid treatment produced an increase in the rapidly digestible starch (RDS) (20.2%) and slowly digestible starch (29.7%), but a decrease in the resistant starch (36.3%) content, as compared with its native counterpart. However, over the longest acid-treatment time, a decrease in the RDS over 5 days was observed. The lintnerized banana starch can be used in food products without additional cooking. The temperature (77–80°C) and enthalpy (11.6–14.1 J/g) of gelatinization increased signiﬁcantly when the acid-treatment time increased, indicating an arrangement of the crystalline lamella by the double helices of the amylopectin chains. The acid treatment increased the retrogradation rate of the lintnerized banana starch gels. The lintnerization of banana starch for different lengths of time modiﬁed its morphology, starch digestibility, and thermal features, indicating changes in the crystalline lamella due to the arrangement of the double helices of amylopectin.
Lintnerization of banana starch isolated from underutilized variety: morphological, thermal, functional properties, and digestibility Lintnerización del almidón de plátano aislado a partir de una variedad subutilizada: propiedades morfológicas, térmicas, funcionales y de digestibilidad
Keywords: Almidón de plátano; lintnerización; Calometría diferencial de barrido